Two cases of a perforated duodenal diverticulum after gastrectomy with Roux-en-Y reconstruction - Shusuke Yagi; Satoshi Ida; Manabu Ohashi; Koshi Kumagai; Naoki Hiki; Takeshi Sano; Souya Nunobe (Surgical Case Reports, 2019)
Abstract Background What type of reconstruction procedure should be applied is one of the important issues in surgery for gastric cancer. We have several options for reconstruction procedure after distal gastrectomy. The Billroth II and Roux-en-Y reconstruction have a duodenal stump while the Billroth I does not have it, which is the biggest structural difference in these procedures. An increase in intraduodenal pressure due to the formation of duodenum stump occasionally causes severe complication such as duodenal stump leakage; however, a duodenal diverticulum perforation after the Roux-en-Y reconstruction has not yet been reported. Herein, we report two cases of a perforated duodenal diverticulum after gastrectomy with the Roux-en-Y reconstruction. Case presentation The first case was a 66-year-old man who presented to our hospital with an acute onset right-upper-quadrant abdominal pain. He had undergone laparoscopic distal gastrectomy with the Roux-en-Y reconstruction for the early gastric cancer 15 months before. A large periampullary diverticulum had been detected during the checkup before the gastrectomy. Abdominal contrast-enhanced CT showed a retroperitoneal fluid collection with gas present at the second part of the duodenum. Therefore, a perforated duodenal diverticulum with abdominal abscess was diagnosed, and an emergency laparotomy was performed. Pancreaticoduodenectomy was performed because of severe duodenal inflammation and surrounding tissue damage. The second case was a 52-year-old man who had undergone open distal gastrectomy for locally advanced gastric cancer. Multiple non-ampullary duodenal diverticula had also been identified during the preoperative checkup. On the 2nd postoperative day, he presented with a sudden-onset abdominal pain with peritoneal irritation signs, and intestinal fluid was identified through the intraperitoneal drainage tube placed in a suprapancreatic site during his previous gastrectomy. Therefore, an emergency laparotomy was performed. During laparotomy, a perforated diverticulum at the second part of the duodenum was detected. The perforated duodenum diverticulum was directly sutured with drainage of the retroperitoneal space. Conclusions It is necessary to recognize that the Roux-en-Y reconstruction after gastrectomy for gastric cancer patients with duodenal diverticulum might cause a perforation of the diverticulum.